The Prevalence of Multimorbidity Among Adults Aged 40 Years and Above in Primary Care Setting: A Cross-Sectional Study - AKMAN, MEHMET (DUZCE UNIV, FAC MEDICINE, 2021)
Objective: Coordination function of primary care (PC) enables continuous, efficient, and cost-effective health care provided to patients with chronic disease and multimorbidity (MM). The aim of this study was to identify the most common chronic diseases and to determine the prevalence of MM in PC registries. Methods: Our study is a cross-sectional study. All the individuals aged 40 and over who were registered to the primary care units (PCUs) of the Uskudar district of Istanbul have formed the population of the study. A systematic cluster sampling was used. The patient list of each family physician in Uskudar district was accepted as a cluster and an equal number of patients from each cluster were enrolled. Only the information on the patients' MM data was requested from the primary care physicians. Results: The 108 physicians of the Uskudar district (response rate: 73.4%) gave consent to participate in the study. The 1187 (40.3%) of registered patients of all PCUs were 40 years old and over. The multimorbid patients were found as 330 (27.8%). Conclusions: Approximately, one of four patients have multimorbidity. So, the policy of primary care services should be redesigned for the management of MM patients including the `goal-oriented care' approach.
Keywords: Multimorbidity; Physicians; Primary Care; Prevalence; Health Policy; HEALTH-CARE